2014
DOI: 10.1177/0163443714523813
|View full text |Cite
|
Sign up to set email alerts
|

Networked technologies as emotional resources? Exploring emerging emotional cultures on social network sites such as Facebook and Hi5: a trans-cultural study

Abstract: This trans-cultural study deals with the question whether social network sites (SNS) may be considered 'third places', where young people find an unrestricted space for self-expression and reflection apart from formal environments (such as universities) and parental control, as well as whether the perception and adoption of such services varies among different cultural communities. To assess these questions, group discussions, qualitative interviews (n = 25) and an online survey (n = 757) were conducted in Tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…experiencing pleasant emotions when in Facebook) affected user loyalty towards the platform. Köhl and Götzenbrucker (2014) found that social media users tend to experience positive emotions such as warmth and cosiness when interacting with their preferred social media platforms and that these platforms allow users a form of self-expression. Similarly, Oh et al (2014) observed that social media use has favorable psychological implications in that positive affect (emotions) experienced by social media users was positively associated with perceived life satisfaction.…”
Section: Ejm 536mentioning
confidence: 99%
See 1 more Smart Citation
“…experiencing pleasant emotions when in Facebook) affected user loyalty towards the platform. Köhl and Götzenbrucker (2014) found that social media users tend to experience positive emotions such as warmth and cosiness when interacting with their preferred social media platforms and that these platforms allow users a form of self-expression. Similarly, Oh et al (2014) observed that social media use has favorable psychological implications in that positive affect (emotions) experienced by social media users was positively associated with perceived life satisfaction.…”
Section: Ejm 536mentioning
confidence: 99%
“…From a practical standpoint, we offer a mechanism through which CBBE is generated in social media platforms per se. There is an increasing recognition that social media platforms are virtual "third places" (Köhl and Götzenbrucker, 2014;McArthur and White, 2016) where consumers congregate and spend significant amount of time. Our findings clearly inform social media practitioners about how user emotional attachments culminate into CBBE development in such virtual gathering sites that have become integral to users; our results have far reaching implications for ongoing usage and loyalty towards these platforms.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, weak-tie relationships are more vulnerable to emotion work as people strategically adjust their emotions and behaviours to cater to the complicated and unfamiliar feeling rules in the given mediated culture (e.g. Köhl and Götzenbrucker, 2014).…”
Section: Emotion Work and Feeling Rulesmentioning
confidence: 99%
“…The technology of social networks creates imagined communities of emotions, communities that experience emotions together (Köhl and Götzenbrucker, 2014). The opportunity to comment in real time allows viewers to exchange opinions and enhances one of the most important features of the radio, which is to encourage discourse (Pease and Dennis, 1993).…”
Section: Initiating a Fruitful Debate And Bilateral Communicationsmentioning
confidence: 99%